Externalities in a Regulated Industry: The Aircraft Noise Problem - Muskin, Jerold B.; Sorrentino, John A. (American Economic Review, 2016)
Airline noise is an externality in the traditional sense of being a byproduct of normal economic activity. It affects the population around airports in single-event bundles and cumulatively. The transient nature of noise itself is unlike most other externalities. As with the others, however, general improvements in technology and increases in population have made the situation more difficult to tolerate. The combination of these things has led to a critical situation for the affected population since it involves its physical and mental health. From among the various methods of dealing with externalities, we choose the effluent charge scheme. It generally allows each firm to incorporate the environmental standard into its marginal operating choices. If each firm makes efficient decisions, then the cost to society of achieving an environmental standard will be a minimum. In this paper, there are two modifications of the traditional charge scheme. One is that because of the well-known difficulties in specifying and estimating social costs, we use the (estimated) direct noise abatement costs of achieving the environmental standard. The second is that airlines cannot be necessarily thought of as cost minimizers. The charges used for the control of airline noise are generated as shadow prices in a simple linear programming model. Solution to the problem involves choosing a mix of noise-abating options that achieves proposed environmental standards at least cost. Additional bounds on the problem are limitations on service reductions and rate-of-return (ROR) oni investment regulation. The data sources used for the program were generally fragmentary and incomplete for our purposes. After calculating a noise charge for a hypothetical airport, we discuss the implementation and ramifications of the charge plan in the regulated airline industry. Included is a discussion of the link between noise abatement and fuel consumption.